Outcome of infants of HIV positive mothers following administration of nevirapine drops at secondary level referral centre - Dr. B.V. Ravi Chandra; Dr. K. Prudhvi Krishna; Dr. Viswanath NGV (Pediatric Review: International Journal of Pediatric Research, 2019)
Introduction: Prevention of transmission of HIV to new born and infants through the integration of preventive and care measures. Objective: To assess HIV transmission, adverse reactions and morbidity among neonates and infants born to HIV positive mothers till 18months of age over a period of 10 years by prevention of mother to child transmission of HIV. Methods: The study was conducted atDepartment of Obstetrics and Gynecology and Department of Paediatrics, secondary level referral centre, MCH block, District hospital, Vizianagaram, Andhra Pradesh, India. The data was collected during May2009 to May 2018 from records of maternal details registered at PPTCT clinic as well as list of infants undergoing Early Infant Diagnosis (EID) recorded in the standard format as per instructions from National AIDS Control Organization (NACO) of India.The study was based on administration of Nevirapine drops and Cotrimoxazole syrup as per the guidelines of National AIDS Control Organization (NACO). Results: A total of 68,000 babies were born during 2009 to 2018, of which 63320 were live born, among them 152 were born to HIV positive mothers. All the 152 babies were given Nevirapine drops immediately after delivery followed by cotrimoxazole syrup and tested for HIV antibodies at 6 months, 12 months and 18months of age. Amongst all the babies born to HIV positive mothers, only one baby was HIV reactive, and moreover no baby developed any life threatening adverse reaction in this study. Conclusion:The follow up study of new born babies of HIV positive mothers on Nevirapine drops is found to be effective and may be continued as per the guidelines of NACO.